2011
DOI: 10.1007/s00125-011-2413-0
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial whole-body glycolysis is similar in insulin-resistant and insulin-sensitive non-diabetic humans

Abstract: Aims/hypothesis Insulin resistance is characterised by impaired glucose utilisation when measured by a euglycaemic–hyperinsulinaemic clamp. We hypothesised that, in response to postprandial conditions, non-diabetic individuals would have similar intracellular glycolytic and oxidative glucose metabolism independent of the degree of insulin resistance. Methods Fourteen (seven male) sedentary, insulin-sensitive participants (mean±SD: BMI 25±4 kg/m2; age 39±10 years; glucose disposal rate 9.4±2.1 mg [kg estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
7
1
1
Order By: Relevance
“…These observations, along with those currently presented, are in contrast to a recent study using an analogous method, ingesting 2 H-labeled glucose and measuring appearance of labeled 2 H 2 O in total body water (21). In that study of 28 healthy men and women, divided into insulin resistant versus insulin sensitive subgroups by the median clamp-derived measure of insulin-stimulated glucose disposal, there was no significant difference in the rate of appearance of tracer in body water by insulin resistance status.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…These observations, along with those currently presented, are in contrast to a recent study using an analogous method, ingesting 2 H-labeled glucose and measuring appearance of labeled 2 H 2 O in total body water (21). In that study of 28 healthy men and women, divided into insulin resistant versus insulin sensitive subgroups by the median clamp-derived measure of insulin-stimulated glucose disposal, there was no significant difference in the rate of appearance of tracer in body water by insulin resistance status.…”
Section: Discussioncontrasting
confidence: 95%
“…Our group demonstrated using limb balance methods in humans that the net glucose delivery to skeletal muscle under steady-state conditions did not differ across insulin resistance groupings, suggesting that hyperinsulinemia was sufficient to compensate for this aspect of glucose handling (20). In a recent paper, Galgani and Ravussin (21) studied integrated whole-body glucose metabolism, measuring total carbohydrate oxidation by indirect calorimetry and production of labeled water following ingestion of labeled glucose as part of a traditional 75 gram glucose load. Nondiabetic subjects were studied, divided by clamp-derived insulin sensitivity into insulin resistant and insulin sensitive groups.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a modestly higher but significant glycaemia was also detected in the insulin‐resistant versus insulinsensitive group. However, whole‐body glycolytic and glucose oxidative rates were similar among groups (Fig. ).…”
Section: Novel Insights About the Interaction Between Insulin Secretimentioning
confidence: 81%
“…In the last years, we have focused our interest in the study of glucose metabolism in insulin‐sensitive and insulin‐resistant individuals under fasting, postprandial and insulin‐infused conditions . We observed that during a euglycaemic–hyperinsulinaemic clamp, both impaired intracellular oxidative and non‐oxidative glucose disposal were mostly consequence of insulin resistance .…”
Section: Novel Insights About the Interaction Between Insulin Secretimentioning
confidence: 99%
“…En un estado de RI, la acción de esta hormona a nivel celular está reducida, aumentando la secreción de insulina. Esto permite compensar el defecto en la acción tisular y así mantener la homeostasis glicémica (5) . Este fenómeno da cuenta del estado hiperinsulinémico, el cual es característico en sujetos con RI.…”
Section: Introductionunclassified